Technology catch-up actions for manufacturing companies in Pakistan - Iqbal, Numan (Cranfield University, 2004)
Technological development in manufacturing companies has been considered as a key contributor to the economic development of nations. Research has confirmed that the contribution of technological development to national wealth is more than 50 %. The objective of this research was to explore the steps which could help manufacturing companies in Pakistan to catch-up in technology with the leading companies in the world. The first step was the quantitative measurement of the status of technology in a sample of manufacturing companies in Pakistan through a new survey method. Numerous interviews with experienced senior factory managers in Pakistan then explored the issues, including barriers to technology improvement, their solutions, actions that could promote technology, and stages required for catch-up in technology. Three case studies included in this process helped in understanding the issues. The outputs were the lists of barriers, solutions, and actions, each organised in a new-found framework of issues essential in technology development, and a four-stage technology catch-up path. A survey then ranked the barrier and action factors in order of their importance. The most important ones were compiled in the form of action plans for factory managers and government policy makers. Similar barrier, solution, and action factors were then explored in the literature on manufacturing companies in successful East Asian countries using content analysis, and ranked in order of importance. This also resulted in action plans and a four-stage technology catch-up path. The results from the Pakistan research were then compared with the results from the literature, and combined to develop comprehensive action plans. This research found that catch-up in technology was possible through specific actions in defined directions by the factory managers themselves without explicit help from the government, although such support can be very valuable.